Targeting Steroidogenic Cytochromes P450 (CYPs) with 6‐Substituted 1‐Imidazolylmethylxanthones. (13th April 2016) - Gobbi, Silvia; Hu, Qingzhong; Zimmer, Christina; Belluti, Federica; Rampa, Angela; Hartmann, Rolf W.; Bisi, Alessandra
Abstract: Abnormally high corticosteroid levels are responsible for the onset of serious hormone‐related diseases, and the inhibition of their biosynthesis by targeting cytochrome P450 (CYP) isoforms CYP11B1 and CYP11B2 has emerged as a promising strategy to restore healthy physiological levels of corticosteroids. With the aim of exploiting the xanthone scaffold as a privileged structure in medicinal chemistry and to further explore the chemical space of inhibitors of these CYPs, a small library of imidazolylmethylxanthones was designed based on the results of a previously described compound series. Assuming the capacity for an additional interaction with these enzymes, a properly selected substituent was introduced at position 6 of the xanthone core, maintaining the key imidazolylmethyl moiety at position 1. The 6‐fluoro and 6‐nitro derivatives [1‐(1 H ‐imidazol‐1‐yl)methyl‐6‐fluoro‐9 H ‐xanthen‐9‐one (1 a ) and 1‐(1 H ‐imidazol‐1‐yl)methyl‐6‐nitro‐9 H ‐xanthen‐9‐one (1 d ), respectively] proved to be active in the low nanomolar range, showing selectivity toward the related steroidogenic enzymes CYP19 and CYP17, even if the problem of selectivity between the two CYP11B isoforms remains unsolved. On the other hand, the 6‐chloro derivative 1‐(1 H ‐imidazol‐1‐yl)methyl‐6‐chloro‐9 H ‐xanthen‐9‐one (1 b ) was found to be a fairly potent and somewhat selective CYP19 inhibitor, confirming the versatility of the scaffold. Abstract : Curbing corticosteroids : 6‐substituted‐1‐imidazolylmethylxanthones provide new insight into the role of an appropriately decorated scaffold in the modulation of steroidogenic cytochromes P450 (CYPs). As regards CYP11B isoforms, the establishment of an additional hydrogen bond seems to be crucial for high potency. Two potent inhibitors of these enzymes emerged, active in the low nanomolar range, as well as a relatively good and selective inhibitor of CYP19.